Periodontal disease in Thai patients with rheumatoid arthritis - Khantisopon N. (Blackwell Publishing, 2014)
Aim: To evaluate the prevalence and severity of periodontal disease in patients with rheumatoid arthritis (RA) who attended a rheumatology clinic in a university hospital. Methods: All consecutive patients with RA who attended the rheumatology clinic between June 2009 and January 2010 were asked to enroll in this study. All participants answered questionnaires, which included demographic data, medical history, medications used and smoking habits. A full mouth periodontal examination, including gingival index, plaque index, probing pocket depth and clinical attachment level was performed. Only cases that had at least 20 teeth were included in this study. Rheumatoid arthritis parameters, including number of tender and swollen joints, erythrocyte sedimentation rate, the presence of rheumatoid factor (RF), hand radiographs, Disease Activity Index (DAS) and health status using the Thai Health Assessment Questionnaire (HAQ), were determined. The association between RA parameters and periodontal condition was examined. Results: There were 196 participants (87.2% female) with a mean age of 51.7 ± 9.70 years, mean disease duration of 9.62 ± 7.0 years and mean DAS score of 4.64 ± 1.25. Eighty-two per cent were RF-positive. Moderate and severe periodontitis were found in 42% and 57%, respectively. Higher age, male gender, previous or current smoking and high level of plaque score were associated with severe periodontal disease. No differences in RA parameters were found between groups of patients who had moderate and severe periodontitis. Conclusions: We found a high prevalence of periodontitis in Thai patients with RA. However, there was no association between RA parameters and periodontal conditions. © 2014 Asia Pacific League of Associations for Rheumatology and Wiley Publishing Asia Pty Ltd.